(untitled) (Jurnal Matematika, Statistika dan Komputasi, 2026)
Unit-linked insurance is a life insurance product that combines elements of protection and investment. Hence, the value of the benefits received by policyholders depends on the performance of the underlying investment asset. This study aims to estimate the benefits of a dual-purpose life insurance (endowment) unit-linked policy using the Point-to-Point method and De Moivre’s Law. The Point-to-Point method determines investment results based on changes in stock prices from the beginning to the end of the contract period. At the same time, De Moivre’s Law is applied to calculate the insured’s chances of life and death to determine actuarial benefits. The data used are daily share prices of PT Bank Negara Indonesia Tbk for the period July 2024-June 2025, assuming a risk-free interest rate of 5,25%. The results showed that the stock volatility of 0,378 reflected a moderate level of risk, while the endowment life insurance benefit obtained of 1,43061 resulted in a single premium of IDR 66.809.378. The investment benefits received by the heirs are calculated based on the benefit structure with a minimum warranty limit and a predetermined maximum value (cap). These findings show that the Point-to-Point method provides a transparent, easy-to-understand estimate of benefits and can be a relevant alternative for calculating the value of unit-linked endowment insurance products in Indonesia.